Non Dispersive Chemical Deacidification of Crude Palm Oil in Hollow Fiber Membrane Contactor - Mubiar Purwasasmita; Eryk Bone Pratama Nabu; K. Khoiruddin; I Gede Wenten (Journal of Engineering and Technological Sciences, 2015)
Performance of chemical deacidification of crude palm oil (CPO) using aqueous NaOH solution in a polysulfone hollow fiber ultrafiltration membrane was  investigated. The effects of operating temperature, NaOH concentration and flow rates on percentage of free fatty acids (FFA) removal, oil loss, soap entrainment and overall mass transfer coefficient  were  evaluated. Overall mass transfer coefficients, soap content in oil and neutral oil loss all increased  when the  temperature  was increased from 60 to 70°C due to an increase of the FFA distribution value. A minimum 0.25 N of NaOH or a NaOH to FFA  molar ratio  of about 7.62 was  required to facilitate the expected extraction efficiency. The increased oil flowrate slightly enhanced the solute transport kinetics,  while the  aqueous phase flowrate did not significantly influence deacidification efficiency or mass transfer coefficient. About 97% of FFA removal was achieved within 4 hours. The maximum oil loss observed was 11% and the highest  soap content in the  oil without separation step was 3150 ppm. The values  of the  overall mass transfer coefficient varied  from 2.97Ã—10-7 to 7.71Ã—10-7 m/s. These results show the potential of using the non dispersive membrane contacting process for chemical deacidification of CPO as well as other vegetable oils.